(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of this research is to determine the ethics of administrative services at the Makassar City Population and Civil Registration Office. The type of research used is descriptive qualitative research with phenomenological research type. Data analysis includes data reduction, data presentation, data verification and drawing conclusions. The results of the research show that the ethics of administrative services from 3 aspects, namely Equal Rights, Loyalty and Responsibility, are quite good. This can be seen from (a) Equality, namely the absence of discrimination or nepotism in serving the community who are carrying out population administration. (b) Loyalty, employees have complied with applicable official regulations as closely as possible. (c) Responsibility, this is based on the employee’s responsibility in carrying out and completing their work well.